Randomised clinical trial: the analgesic properties of dietary supplementation with palmitoylethanolamide and polydatin in irritable bowel syndrome. Issue 7 (6th February 2017) - Cremon, C.; Stanghellini, V.; Barbaro, M. R.; Cogliandro, R. F.; Bellacosa, L.; Santos, J.; Vicario, M.; Pigrau, M.; Alonso Cotoner, C.; Lobo, B.; Azpiroz, F.; Bruley des Varannes, S.; et al.
Summary: Background: Intestinal immune activation is involved in irritable bowel syndrome (IBS) pathophysiology. While most dietary approaches in IBS involve food avoidance, there are fewer indications on food supplementation. Palmithoylethanolamide, structurally related to the endocannabinoid anandamide, and polydatin are dietary compounds which act synergistically to reduce mast cell activation. Aim: To assess the effect on mast cell count and the efficacy of palmithoylethanolamide/polydatin in patients with IBS. Methods: We conducted a pilot, 12‐week, randomised, double‐blind, placebo‐controlled, multicentre study assessing the effect of palmithoylethanolamide/polydatin 200 mg/20 mg or placebo b.d. on low‐grade immune activation, endocannabinoid system and symptoms in IBS patients. Biopsy samples, obtained at screening visit and at the end of the study, were analysed by immunohistochemistry, enzyme‐linked immunoassay, liquid chromatography and Western blot. Results: A total of 54 patients with IBS and 12 healthy controls were enrolled from five European centres. Compared with controls, IBS patients showed higher mucosal mast cell counts (3.2 ± 1.3 vs. 5.3 ± 2.7%, P = 0.013), reduced fatty acid amide oleoylethanolamide (12.7 ± 9.8 vs. 45.8 ± 55.6 pmol/mg, P = 0.002) and increased expression of cannabinoid receptor 2 (0.7 ± 0.1 vs. 1.0 ± 0.8, P = 0.012). The treatment did not significantly modify IBS biological profile, including mast cell count. Compared with placebo, palmithoylethanolamide/polydatin markedly improved abdominal pain severity ( P < 0.05). Conclusions: The marked effect of the dietary supplement palmithoylethanolamide/polydatin on abdominal pain in patients with IBS suggests that this is a promising natural approach for pain management in this condition. Further studies are now required to elucidate the mechanism of action of palmithoylethanolamide/polydatin in IBS. ClinicalTrials.gov number, NCT01370720. Abstract : Linked Content This article is linked to Quigley paper. To view this article visithttps://doi.org/10.1111/apt.14014 .